Environmental Toxicity Assessment of Organotin Compounds Using the Direct Contact Bioassay – OSTRACODTOXKIT F - Szwarc, Tomasz; Komasara , Piotr; Mikołajczak , Paweł; Kałwik , Mateusz; Michalak , Mateusz; Bochenek , Hubert; Bzoma , Michał; Nowakowska , Julia; Klepacz , Iga (Quality in Sport, 2025)
The aim of the study was to assess the toxicity of organic compound of tin using two tests with Heterocypris incongruens. Chlorides: tributyltin, trimethyltins and triphenyltin were tested by conducted acute (mortality) and chronic toxicity tests (mortality and length of organisms). The highest acute toxicity were obtained by TBT (LC50=0.113 ppm) and TPT (LC50=0.167 ppm), while the lowest was TMT (LC50=1.76 ppm). In chronic lethal effect was caused by the same TPT concentration (above 0.1 ppm), whereas different results were obtained for TBT (mortality in concentrations over 10-times higher), which may be due to strong binding of compound with sediment